2018
DOI: 10.3390/s18103443
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Sensing Technologies for Next-Generation Cyber-Physical Systems

Abstract: Carbon monoxide (CO) is a toxic gas, and environmental pollutant. Its detection and control in residential and industrial environments are necessary in order to avoid potentially severe health problems in humans. In this review paper, we discuss the importance of furthering research in CO sensing technologies for finding the proper material with low-range detection ability in very optimum condition. We build our discussion through the perspective of a cyber-physical system (CPS) modeling framework, because it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 107 publications
(156 reference statements)
1
69
0
Order By: Relevance
“…The three main characterization parameters for the performance of any sensor are sensitivity, response time, and recovery time. Response time is the time for responding to a step concentration change from 0 to 90% of the saturated value and recovery time is the time taken for the signal of the sensor to return to 90% of the initial value [ 50 ]. From the results in Figure 8 a,b, it is observed that the eight sensor array coated with the sensing material of SnO 2 and 0.2% Pd, gives 11.6 mV, compared to 4.1 mV in three sensor array, which is because of the additive effect of the potential.…”
Section: Resultsmentioning
confidence: 99%
“…The three main characterization parameters for the performance of any sensor are sensitivity, response time, and recovery time. Response time is the time for responding to a step concentration change from 0 to 90% of the saturated value and recovery time is the time taken for the signal of the sensor to return to 90% of the initial value [ 50 ]. From the results in Figure 8 a,b, it is observed that the eight sensor array coated with the sensing material of SnO 2 and 0.2% Pd, gives 11.6 mV, compared to 4.1 mV in three sensor array, which is because of the additive effect of the potential.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanotubes received enormous attention over the last three decades due to their unique electrical, mechanical, and optical properties [25][26][27][28][29][30][31][32][33][34]. CNTs are capable of altering LC matrix chemistry, viscosity, dispersion quality, etc.…”
Section: Review On Condutivity Behavior Of Lc-cnt Dispersionsmentioning
confidence: 99%
“…Another important issue is creation of residential and automotive environment so it is so necessary fast and sensitive detection. Difficulty in detecting very low levels and continuous CO formation in the air poses problems [5].…”
Section: Introductionmentioning
confidence: 99%